2013
DOI: 10.1002/2013ja019290
|View full text |Cite
|
Sign up to set email alerts
|

Current structures associated with dipolarization fronts

Abstract: [1] Recently, observational results on currents around the dipolarization fronts (DFs) of earthward flow bursts have attracted much research attention. These currents are found to have close association with substorm intensifications. This paper devotes to further study of the current system ahead and within the DFs with high-resolution magnetic field measurements from Cluster constellation in 2003. The separation of four spacecraft is much smaller than the scales of spatial structures ahead and within the DF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 64 publications
(110 citation statements)
references
References 26 publications
(43 reference statements)
13
89
3
Order By: Relevance
“…4 that was not shown in the current system described in Fig. 4b by Yao et al (2013), we suggest this pressure increase may be caused by the compression of the plasma flow behind the DF. This dawnward current is naturally expected from Fig.…”
Section: The Re-distribution Of Cross-tail Current Densitymentioning
confidence: 50%
See 3 more Smart Citations
“…4 that was not shown in the current system described in Fig. 4b by Yao et al (2013), we suggest this pressure increase may be caused by the compression of the plasma flow behind the DF. This dawnward current is naturally expected from Fig.…”
Section: The Re-distribution Of Cross-tail Current Densitymentioning
confidence: 50%
“…This B z signature is seen for all distance ranges shown in the figure. Yao et al (2013) showed that such a dip in the magnetic field ahead of DFs is a common, and found that field-aligned currents usually exist in this region. We now compare DFs based on the magnitude of the change in B z prior to the DF arrival.…”
Section: Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…The current disruption started at the leading edge of the flow, as a sharp dipolarization front (DF) with a magnetic dip ahead of the front layer. The magnetic dip current, which is of Region 2 sense, has been studied recently [Liu et al, 2013a[Liu et al, , 2013bYao et al, 2013b;Sun et al, 2013]. Those studies presented the FAC features ahead of the DF, while this paper has studied the cross-tail current density evolution ahead of earthward flow.…”
Section: Discussionmentioning
confidence: 99%